Impact of organization culture, workplace flexibility and compensation on Generation Y employees’ retention at BRAC - Lubaba, Wahiba Kawser (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.